JAK-STAT pathway inhibitors in dermatology - Miot, Hélio Amante [UNESP]; Criado, Paulo Ricardo; de Castro, Caio César Silva; Ianhez, Mayra; Talhari, Carolina; Ramos, Paulo Müller [UNESP] (Elsevier, 2023)
The JAK-STAT signaling pathway mediates important cellular processes such as immune response, carcinogenesis, cell differentiation, division and death. Therefore, drugs that interfere with different JAK-STAT signaling patterns have potential indications for various medical conditions. The main dermatological targets of JAK-STAT pathway inhibitors are inflammatory or autoimmune diseases such as psoriasis, vitiligo, atopic dermatitis and alopecia areata; however, several dermatoses are under investigation to expand this list of indications. As JAK-STAT pathway inhibitors should gradually occupy a relevant space in dermatological prescriptions, this review presents the main available drugs, their immunological effects, and their pharmacological characteristics, related to clinical efficacy and safety, aiming to validate the best dermatological practice.
Keywords: Alopecia areata; Atopic dermatitis; Janus Kinase Inhibitors; Psoriasis; Treatment; Vitiligo